ON THE QUESTION OF LEGAL NIHILISM - Arman Sericovitch Ахметов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
In the present article the basic questions of the study of legal nihilism. The author of the article on the basis of domestic and foreign source reveals approaches to the definition of legal nihilism as a social phenomenon. In the process of writing the article touched on the essence and nature of legal nihilism and the proposed methods to combat this phenomenon. In addition, the author shows how urgent this issue for the development of the entire legal system and increase the level of legal culture of the population. In conclusion, the author notes that the need for further research to address this issue in light of the formation of a civil society and a democratic state.